Experimental study on effects of nozzles and combustors on the rotating detonation rocket engine in pulse operation - Guining Liu; Zixuan Wang; Yingying Ruan; Zewen Zhong; Rui Wang; Shengbing Zhou; Ning Hu (Results in Engineering, 2025)
The rotating detonation engine (RDE) is an innovative pressure-gain combustion device that harnesses detonation waves for efficient fuel combustion. This paper examines the impact of various nozzle and combustor configurations on the operating characteristics of a rotating detonation rocket engine (RDRE) with a pulse operating frequency of 10 Hz. Through experimental analysis,the study investigates the propagation mode and establishment process of rotating detonation waves (RDWs) and the thrust performance across seven different engine structures to identify the optimal combination. The results show that the detonation-wave velocity and stability of cavity combustor are optimal, and the stability of detonation-wave propagation improves with an increasing equivalence ratio. The establishment time of the detonation wave is <10 % of the single pulse duration. At similar equivalence ratios, the RDRE featuring an annular combustor and a plug nozzle achieves the swiftest establishment at under 1 ms. The detonation-wave propagation velocity in RDREs exhibits significant differences between nozzle configurations: 2.1 km/s for Laval nozzles versus 1.8 km/s for plug nozzles. The RDRE with a Laval nozzle has higher detonation-wave propagation velocity than that of the plug nozzle structure. Furthermore, integrating a laval nozzle and a cavity combustor in a high-pulse-frequency operation significantly enhances the engine's propulsion performance. This research aspires to offer valuable insights for the utilization of RDREs in spacecraft attitude control applications.